Lesene ovojne konstrukcije v Alpah, s poudarkom na slovenski alpski arhitekturi - Križaj, Eva (Les (Ljubljana), 2006)
Alpine architecture must conform to extreme climate and relief, while assimilating with the natural surroundings at the same time. Covering structures analysis showed, that this has been known and taken into consideration by the early builders in the intact alpine environment. From those building shelter places, huts for shepherds, choppers and charcoal burners, to the ones who were building mountain huts. The only exception is a bivouac with its unique shape, independent from the characteristics of the regional environment. Shelters and huts were mostly made from local materials, from wood as a rule. Although there has been a big change in the building technique due to modem technology, wood still holds its position as the prevailing construction material. European mountain architecture is much alike regardless of different countries, while it is driven by climate and relief characteristics. It can be distinctively didtinguished only in contrast with the architecture in the valeys.
Keywords: alpska arhitektura; lesene konstrukcije; planinske koče; Slovenia; Slovenija